ANALISIS ANGGARAN PENDAPATAN BELANJA DAERAH KABUPATEN REMBANG TAHUN 2007 - Tahwin, Muhammad; Hastuti, Setyo (Potensio, 2009)
Abstract The proportion of local revenue (PAD), Rembang against budget on average over three years from 2005 to 2007 was low, amounting to 6.79%. Thus, Rembang dependence on central government is still very large which is reflected in the amount of fund balance averaged over the three years 2005- 2007 amounted to 88.66%. In the year 2007 Apex district budget deficit, so we need alternative measures to reduce the level of deficit and dependence on the center include: policies to increase local revenue and spending policies are more selective with based on performance.Keyword: Regional Shopping Revenue Budget, Rembang District